Agroecosystem diversification for sustainability : the effects of crop rotation on soil microbial diversity, fertility and yield - Venter, Zander Samuel (Stellenbosch : Stellenbosch University, 2016)
Thesis (MScAgric)--Stellenbosch University, 2016.